Immersive learning through virtual reality for civil engineering education - Kuncoro, Tri; Ichwanto, Muhammad Aris; Dwiyanto, Felix Andika (LPMPP Universitas Negeri Yogyakarta, 2025)
This academic work focuses on creating and assessing a Virtual Reality (VR) learning tool designed for civil engineering education. The tool aims to help students understand complex construction phenomena better by providing laboratory and real-world simulation-based construction scenarios. With the aid of immersive learning offered by VR, the gap between theoretical and practical knowledge is narrowed, and issues such as limited site access, safety requirements, and logistical challenges are mitigated. The study employs a systematic approach to development, including needs identification, tool creation, and evaluation after the tool is developed. The use of paired t-tests enables quantitative analysis of the data. It reveals improved learning outcomes among students utilizing the developed VR tool compared to traditional methods. In addition, students with VR perception reported high ease of use and satisfaction scores. The results emphasize how VR technology can cultivate critical 21st-century skills like problem-solving, collaboration, creativity, and constructive technological engagement. VR can deliver students with safe, inexpensive, and easy-to-scale solutions that offer a wider range of construction learning that was impossible to provide in the past. This study aids a growing understanding of innovations in teaching and learning technology in civil engineering education, especially the importance of VR in preparing them for Industry 4.0. More research should investigate the sustainability of the impacts of the VR environment on learning among engineers from different specialities.